PENERAPAN PEMBELAJARAN TEMATIK BERBASIS BUDAYA BETAWI UNTUK MENINGKATKAN MUSICAL INTELLIGENCE SISWA SD ISLAM TAMAN QURANIYAH - Fery Muhamad Firdaus; Tria Puspasanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2019)
This study aims to: (1) find out the thematic learning process based on Betawi culture, and (2) improve the musical intelligence of grade IV Islamic elementary schools in the Quraniyah Park through thematic learning based on Betawi culture. Thematic learning based on Betawi culture is the process of learning about culture, learning with culture, learning through culture, even cultured learning, especially Betawi culture. This study uses the Class Action Research (CAR) method. PTK is implemented as an effort to overcome problems that arise in the classroom. This method is carried out in four stages, namely planning, implementation of the action, the effect of monitor implementation and survey / reflection. Data collection techniques using instrument interviews, the results of observation of teacher and student activities, musical intelligence tests, field notes and documentation. The research subjects were 27th grade Islamic elementary school students in the Quraniyah Park, consisting of 14 female students and 13 male students. This research was conducted in 3 cycles. The collected data is analyzed using quantitative and qualitative descriptive. The results of the students' musical intelligence tests in the first cycle were 14 students (52%) who achieved the target with an average grade of 70. In the second cycle it increased to 20 students (74%) who achieved the target with an average grade of 80. Then in the cycle III has increased to 23 students (85%) who have reached the target with 87 class average res